Le federalisme canadien et les subventions aux universite´s que´be´coises - Bellavance, Michel (Canadian Journal of Higher Education, 1980)
The intervention of the Canadian government in financing Quebec universities has taken many forms over the years. Ottawa has been involved in supporting general as well as vocational education, academic as well as para-academic activities and pure as well as applied university research. Such intervention has also followed various paths, Ottawa intervening sometimes through individual or institutional direct or indirect grants, sometimes through operating or investment grants, and sometimes through fiscal transfers. In trying to unravel the complexity of Ottawa-Quebec relations in university education, the article describes the historical evolution of federal grants to Quebec universities. Four periods are singled out, each one representing a crucial turning-point. The picture that one can draw from the development of Ottawa's involvement in higher education becomes less confusing when one is conscious of the fact that it is multiform and, in many respects, inconsistent. The article shows, for instance, how the massive intervention of the central government in financing university research contrasts with the freedom left to the provinces in the area of student loans. It also contrasts the nature of the federal involvement in financing univer-sity investments with the much more important intrusion of the same government in the area of general operating grants. Finally, the author points out that the opposition mani-fested by the Canadian provinces - and especially Quebec - vis-à-vis the many federal initiatives varied from sector to sector. L'article 93 de la Constitution canadienne de 1867 accorde aux législatures provinciales une compétence législative et une responsabilité exclusive en matière d'éducation. Cependant, cette attribution de pouvoir comporte une réserve: le Parlement fédéral est investi du pouvoir d'intervenir, au besoin, pour défendre les droits de certaines minorités.1 Or, malgré cette disposition constitutionnelle, l'intervention du gouvernement fédéral dans le secteur de l'éducation, que l'on peut faire remonter au début du siècle, ne s'est limitée ni à un type, ni à un niveau d'enseignement. Elle s'est manifestée, en effet, tant au niveau élémentaire qu'aux niveaux secondaire, collégial et universitaire. Elle a aussi touché tous les types de formation, qu'il s'agisse de formation générale ou professionnelle, de formation scolaire ou extra-scolaire. Elle a, enfin, emprunté plusieurs voies tantôt prenant la forme de subventions individuelles ou institutionnelles, tantôt la forme de subventions directes ou de transferts fiscaux. C'est dans le but de démêler — un tant soit peu — cet écheveau, que nous nous proposons ici de faire le point sur les divers types d'intervention du gouvernement central dans le secteur de l'enseignement universitaire québécois. L'analyse de l'évolution historique de cette intervention devrait non seulement permettre une meilleure compréhension des relations intergouvernementales dans un secteur souvent considéré comme étant de juridic-tion provinciale exclusive, mais aussi de soulever certaines questions concernant les orientations gouvernementales dans les ann ëes à venir.